Effects of core stochastization on particle and momentum transport. (12th February 2021) - Ohtani, Yoshiaki; Tanaka, Kenji; Igami, Hiroe; Ida, Katsumi; Suzuki, Yasuhiro; Takemura, Yuki; Tsuchiya, Hayato; Sanders, Mike; Yoshinuma, Mikirou; Tokuzawa, Tokihiko; Yamada, Ichihiro; Yasuhara, Ryo; et al.
Abstract: The effects of the stochastic magnetic field in a plasma center produced by electron cyclotron current drive (ECCD) on transport have been revealed. Because the electron temperature profile is flat in the core region, in the case of counter-directed ECCD (ctr-ECCD) against the toroidal magnetic field, the magnetic field is stochastic in the core region with rotational transform ᵼ ∼ 1/3. The particle diffusion coefficient of the ctr-ECCD plasma is approximately 20 times as large as that of the plasma without the stochastic magnetic field produced by co-directed ECCD (co-ECCD) at the maximum. Furthermore, in the stochastic magnetic field with ctr-ECCD, counter-directed intrinsic rotation is observed in the plasma with balanced NBI discharge.